Dominant localization of prostaglandin D receptors on arachnoid trabecular cells in mouse basal forebrain and their involvement in the regulation of non-rapid eye movement sleep - Mizoguchi, Akira (The National Academy of Sciences, 2001)
Infusion of prostaglandin (PG) D(2) into the lateral ventricle of the brain induced an increase in the amount of non-rapid eye movement sleep in wild-type (WT) mice but not in mice deficient in the PGD receptor (DP). Immunofluorescence staining of WT mouse brain revealed that DP immunoreactivity was dominantly localized in the leptomeninges (LM) of the basal forebrain but that PGD synthase immunoreactivity was widely distributed in the LM of the entire brain. Electron microscopic observation indicated that DP-immunoreactive particles were predominantly located on the plasma membranes of arachnoid trabecular cells of the LM. The region with the highest DP immunoreactivity was clearly defined as bilateral wings in the LM of the basal forebrain located lateral to the optic chiasm in the proximity of the ventrolateral preoptic area, one of the putative sleep centers, and the tuberomammillary nucleus, one of the putative wake centers. The LM of this region contained DP mRNA 70-fold higher than that in the cortex as judged from the results of quantitative reverse transcription–PCR. PGD(2) infusion into the subarachnoid space of this region increased the extracellular adenosine level more than 2-fold in WT mice but not in the DP-deficient mice. These results indicate that DPs in the arachnoid trabecular cells of the basal forebrain mediate an increase in the extracellular adenosine level and sleep induction by PGD(2).